2007
DOI: 10.1111/j.1469-8986.2007.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the error negativity reflect response conflict strength? Evidence from a Simon task

Abstract: The error (-related) negativity (Ne or ERN) has been related to detecting the mismatch between incorrectly executed and appropriate responses or, alternatively, to the degree of conflict between different response alternatives. In this study different levels of response conflict were generated by manipulating task difficulty in a Simon task. According to the product of incorrect and subsequent correct EMG activation, the amount of conflict in error trials was indeed larger for the easy than for the hard condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 28 publications
11
32
0
Order By: Relevance
“…The present experiment replicated the common finding that RTs are shorter in error trials than in correct trials (e.g., Falkenstein, 2004;Masaki et al, 2007). This suggests that errors are due to premature responding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present experiment replicated the common finding that RTs are shorter in error trials than in correct trials (e.g., Falkenstein, 2004;Masaki et al, 2007). This suggests that errors are due to premature responding.…”
Section: Discussionsupporting
confidence: 90%
“…These studies have in common that the degree of response conflict was defined by peripheral measures such as electromyography (EMG; Burle et al, 2005;Masaki et al, 2007) or button press force (Carbonnell & Falkenstein, 2006).…”
Section: Ernmentioning
confidence: 99%
“…Thus, the motor response interference deWned by the task cannot be a sole determiner. This is consistent with other types of data indicating that the computational model itself does not pass some basic empirical tests (Burle, Roger, Allain, Vidal, & Hasbroucq, 2008;Masaki, Falkenstein, Sturmer, Pinkpank, & Sommer, 2007;Masaki & Segalowitz, 2004).…”
Section: Implications For the Modelsupporting
confidence: 86%
“…Previous studies suggest that the ERN and CRN are not modulated error awareness (Endrass et al, 2007;Nieuwenhuis et al, 2001). Results regarding the influence of error rates are mixed and some demonstrated larger ERNs associated with lower error rates (Holroyd & Coles, 2002;Pailing & Segalowitz, 2004a) and others reported no relationship between error-rate and ERN (Falkenstein, Hoormann, Christ, & Hohnsbein, 2000;Masaki, Falkenstein, Sturmer, Pinkpank, & Sommer, 2007). In our study the reported difficulty effects on ERN and CRN were replicated when controlling for differences in error rates 3 .…”
Section: Error Reaction Time (Ms)supporting
confidence: 68%